Letter (copy) : Basque Children - Tewson, Vincent
1941-03-10 038-0034-001 Secretary's HVT/FC/KA/441 10th March 1941 Mr. E.J. Butler, Basque Children Fund, 5 Alton Terrace, North Hill, Plymouth. Dear Mr. Butler, BASQUE CHILDREN I am in receipt of your further letter of the 26th February, and am afraid that I cannot promise any further assistance to Plymouth. There is little I can add to my letter of 12th September last. It is true that recently, with the extraordinary responsibility we have had to face with the Spanish seamen - a responsibility which still continues - we have not been able to assist the National Committee for Basque Children as we did when funds were available. It may interest you to know, however, that we have given help to the extent of £5,810, but as we have the undivided responsibility for Spanish seamen it is an extremely heavy burden. In view also of the fact that the Spanish Fund has long since been exhausted we are unable to do more at the moment. In any case it is quite impossible for a national organisation such as ours to make grants to any local committee. Yours sincerely, Assistant Secretary 292/946/38/34(I)